Binsabin dan Tongngebban as Madurese Local Wisdom: An Anthropology of Islamic Law Analyses - Suhaimi Suhaimi; Agustri Purwandi; Akhmad Farid Mawardi Sufyan (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2021)
There is a unique tradition in the Madurese community of East Java, namely Binsabin and Tongngebban. Both are the absolute requirements for a valid engagement. It means that the engagement is not totally legal without the two things. In the perspective of Islamic law, this is permitted, but from an anthropological perspective, found that there is a social inheritance that is imposed on social bonds, the rules of marriage law and ceremonies in the marriage process. In line with that, this paper wants to describe a local wisdom in a proportional framework, not only seeing society legally, but also society must be seen as a culture (anthropology). This paper is collected from data interviews with two different types of community groups. The results of the study show that first, from an anthropological perspective; the binsabin and tongngebban traditions express the fulfillment of individual psycho-biological needs and maintain the continuity of life of social groups. Anthropology also shows strong the Madurese community is in upholding this tradition from generation to generation even though times round and round. Second, in the perspective of Islamic law, this tradition seeks to build three things, first building a strong agreement between fellow Muslim families, second establishing friendship so as to create a strong emotional bond, third sharing the joy that shown by giving gifts or goods so as to increase the strength of brotherly bonds by religious way (engagement).